2012
DOI: 10.1111/j.1743-6109.2012.02704.x
|View full text |Cite
|
Sign up to set email alerts
|

WNT2 Locus is Involved in Genetic Susceptibility of Peyronie’s Disease

Abstract: Introduction Peyronie’s disease (PD) is a fibromatosis of the penis, with a pathology very similar to what is seen in the hand (palmar fascia) in Dupuytren’s disease (DD). Recently, we performed a genome-wide association study and identified nine genetic loci containing common variants associated with DD. Seven of these loci mapped within or near genes of the canonical WNT pathway and each locus yielded relatively large odds ratios (ORs) for DD disease status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 21 publications
0
29
1
3
Order By: Relevance
“…In order to determine whether these SNPs were also present in men with PD, allele frequencies for the SNPs were assessed among 111 men with PD and compared to 490 unaffected controls. 45 Of the SNPs evaluated, a statistically significant association was observed with SNP rs4730775 at the WNT2 locus on chromosome 7. Taken together, these studies further implicate a common set of genetic factors for both PD and DD.…”
Section: Single Nucleotide Polymorphisms Associated With Pd and Ddmentioning
confidence: 92%
“…In order to determine whether these SNPs were also present in men with PD, allele frequencies for the SNPs were assessed among 111 men with PD and compared to 490 unaffected controls. 45 Of the SNPs evaluated, a statistically significant association was observed with SNP rs4730775 at the WNT2 locus on chromosome 7. Taken together, these studies further implicate a common set of genetic factors for both PD and DD.…”
Section: Single Nucleotide Polymorphisms Associated With Pd and Ddmentioning
confidence: 92%
“…The lesion caused by PD consists of a scar containing a large amount of collagen and fibrin, but the exact etiology is uncertain. Currently the most credible etiopathogenetic theories are: the genetic hypothesis [5,6] (PD is often associated with Dupuytren's disease (palmar aponeurosis), which is histologically similar and identified by an autosomal dominant gene with variable expressivity);…”
Section: Introductionmentioning
confidence: 99%
“…Familiar aggregation and genetic transmission through HLA-B7 antigens had been amply described and understood [68]. Recently, a genetic locus that PD shares with Dupuytren's contracture was identified; WNT2 is the locus involved in genetic predisposition for both Dupuytren's disease and PD [9]. Previously, some studies had already observed the analogy and strong affinity between the two diseases: Dupuytren's contracture's typical cells with “cross-banded” nuclei had been observed in PD plaques in 1976; in 1989, Somers et al, after histological examination of PD plaques, proved an increase in type III collagen content, similarly to what occurs in Dupuytren's contracture [10, 11].…”
Section: Introductionmentioning
confidence: 99%